Trends in book selection policies in selected school libraries in Manila and Quezon City, Philippines - Dimaisip, Joyce Jazmin G. (2001)
The study is titled "Trends in Book Selection Policies in Selected School Libraries in Manila and Quezon City, Philippines." The school libraries included in the study are University of the Philippines Integrated School Library, San Sebastian high school library, Lourdes School of Quezon City high school library and School of the Holy Spirit of Quezon City school library. The objectives of the study are the following: 1) To be able to know if there is an established system of book selection in school libraries in Manila and Quezon City; 2) to be able to know what are the trends in book selection in school libraries in Manila and Quezon City; and 3) to mark differences in the changes in trends in book selection in school libraries in Manila and Quezon City for the past three decades.